Pengaruh Film Animasi adit dan Sopo Jarwo terhadap Perkembangan Moral - Luluk Nurmawati (JURNAL INOVATIF ILMU PENDIDIKAN, 2019)
This Objective of this research was description the effect of the animated film "Adit and Sopo Jarwo" on moral development in children of group B kindergarten Dharma Wanita Gentong Paron Ngawi Academic Year 2018/2019. This research method uses pre-experimental design with one-group type pre-test post-test design. The subjects of the study were Children of group B of the Dharma Wanita Gentong Paron Ngawi Kindergarten, with 15 children consisting of 9 boys and 6 girls. Data collection techniques are observation, interviews and documentation. Data analysis techniques used parametric statistics with the t test or t-test for small samples that are interconnected. The results of this study indicate that there is an increase in the average score of the moral development of children of group B before and after treatment, ie 48.21 to 70.83. i.e. shows that t_ (count) = 7.68 and t_table = 2.14 where t_ (count) t_tabel (7.68 2.14) so that the null hypothesis (H_0) is rejected while the alternative hypothesis (H_a) is accepted. It can be concluded that there is a significant influence of the animated film "adit and sopo jarwo" on moral development in group B kindergarten children Dharma Wanita Gentong Paron Ngawi.Keywords: Moral Development, "Adit and Sopo Jarwo" Animated Film DOI: http://dx.doi.org/10.23960/jiip.v1i2.21783